The Clinical Importance of Campylobacter concisus and Other Human Hosted Campylobacter Species - Liu, Fang; Ma, Rena; Wang, Yiming; Zhang, Li (Frontiers in Cellular and Infection Microbiology, 2018)
Historically, Campylobacteriosis has been considered to be zoonotic; the Campylobacter species that cause human acute intestinal disease such as Campylobacter jejuni and Campylobacter coli originate from animals. Over the past decade, studies on human hosted Campylobacter species strongly suggest that Campylobacter concisus plays a role in the development of inflammatory bowel disease (IBD). C. concisus primarily colonizes the human oral cavity and some strains can be translocated to the intestinal tract. Genome analysis of C. concisus strains isolated from saliva samples has identified a bacterial marker that is associated with active Crohn's disease (one major form of IBD). In addition to C. concisus, humans are also colonized by a number of other Campylobacter species, most of which are in the oral cavity. Here we review the most recent advancements on C. concisus and other human hosted Campylobacter species including their clinical relevance, transmission, virulence factors, disease associated genes, interactions with the human immune system and pathogenic mechanisms.